Spiritual beliefs and eschatological salvation of the Lao: An analysis of the four palm leaf manuscripts and words of holy men during the early twentieth century - Ryota Wakasone (2018)
© 2017, Center for Southeast Asian Studies. All rights reserved. In their research on the “Holy Man’s Rebellion,” a millenarian movement that occurred in Thailand and Laos during the early twentieth century, historians have uncovered the concept of eschatology and belief in Maitreya. However, the idea of the eschatological salvation of the Lao, as derived from the Four Palm Leaf Manuscripts, has not yet been revealed. In addition, we do not know whether the Holy Man’s Rebellion, in accordance with the tenets of Buddhism, was what influenced the spiritual belief systems of Lao society. Hence, in this study, we aim to reveal the concept of eschatological salvation and its connection with Cakkavatti, as well as the historical meaning of the Holy Man’s Rebellion, in the context of Lao spiritual beliefs. We achieve this aim by analyzing the Four Palm Leaf Manuscripts that were handed down to temples, and also through the holy men’s preaching to the Lao. We found that the eschatological savior of the Lao in the beginning of the twentieth century was a Cakkavatti; this belief was reflected in the divine right of kings. Furthermore, the holy men considered spiritual beliefs as being lower than Buddhist beliefs. This suggests that the words of holy men, who spoke hierarchically about Buddhism and spiritual beliefs, were spread among a wide range of peoples and became embedded within Lao society. Therefore, we discovered that there was significant meaning to the Lao’s thoughts about subjectivity as well as the historical significance of the Holy Man’s Rebellion.